Self-service kiosks in fast food restaurants: a study on customers' usage intentions / Siti Nur Syahida Mohd Shukry ... [et al.] - Mohd Shukry, Siti Nur Syahida; Mazlan, Suhada Nazira; Abdul Latip, Muhammad Safuan; Mohamad, Mohamad Amiruddin; Azeman, Ainnin Sofea (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2023)
This study examines the determinants of usage intention on self-service kiosks in fast food restaurants in Malaysia. The five factors incorporated in this study are performance expectancy, effort expectancy, social influence, promotion, and attitude. Partial Least Square-Structured Equation Modeling (PLS-SEM) has been employed to analyze the framework based on survey data collected from 196 respondents. The analysis confirms that only effort expectancy, promotion, and attitude toward technology significantly influence the usage intention of self-service kiosks in fast food restaurants. This study also confirms that the UTAUT (Unified Theory of Acceptance and Use of Technology) can be modified with new variables to predict consumers' intention to use technology in the fast-food industry. The outcome of the study provides insights and theoretical contributions in developing theories, as well as practical implications for the food and beverage industry. Additionally, this study recommends several potential directions for future research.